Analisa Dan Desain Sistem Informasi Pengadaan Barang Pada PT Java Abadi Gemilang Dengan Metodologi Berorientasi Obyek - Adzi Pangestu; Achmad Baihaqi; Junaedi Junaedi (Prosiding, 2022)
PT Java Abadi Gemilang is a service company for an IT company. One of its business activities is the procurement of goods. The current procurement process is still carried out conventionally, so problems often arise, including difficulty in finding data/files, errors in recording and counting, and making old reports. Based on these problems came the idea of ​​designing a computerized procurement information system. The research methodology used is to identify needs by collecting data through interviews with the purchasing department, direct observation by observing the activities of the purchasing department, studying literature by conducting literature reviews of books and previous similar research, and analyzing current documents in the purchasing department. . Then from the collected data, business process analysis is carried out which is described by activity diagrams. Based on business process analysis, problem analysis was conducted using Cause Effect Diagram. So it can be described needs analysis with use case diagrams. Then we get an overview of the data model in the form of an Entity Relationship Diagram (ERD) which is then transformed into a Logical Record Structure (LRS). Based on the results of the analysis, a system design design is then made in the form of an output design and an input design. Then proceed with translating the design into the VB.NET programming language and MySQL database, until it becomes a procurement system. The waterfall model is used as a system development method. With the procurement of goods information system, the procurement process becomes more effective